(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: To study clinical presentation of umbilical and paraumbilical hernia in adults. Materials & methods: A total of 150 subjects were enrolled. The age group included was 26- 50 years. 100 subjects were female and 50 were male. Complete medical history was taken. Patients with umbilical and paraumbilical hernia were taken under consideration. Data was collected and analysed. Results were assessed using SPSS software.Results: A total of 150 patients were enrolled. Clinically, the sites of hernia studied were the umbilical and paraumbilical hernia. The most common is the paraumbilical with frequency of 98 (65.4%) and umbilical hernia with 52 (34.7%). The size of hernia was small with 112 and moderate or huge with 38 cases.Conclusion: From the above results, the authors conclude that small Paraumbilical hernia are more common in comparison to umbilical hernia.